Development of decellularized conjunctiva as a substrate for the ex vivo expansion of conjunctival epithelium. (12th June 2017) - Kasbekar, Shivani; Kaye, Stephen B.; Williams, Rachel L.; Stewart, Rosalind M.K.; Leow‐Dyke, Sophie; Rooney, Paul
Abstract: This study was performed to develop a method to decellularize human conjunctiva and to characterize the tissue in terms of its deoxyribose nucleic acid (DNA) content, tensile strength, collagen denaturation, basement membrane, extracellular matrix components and its potential to support conjunctival epithelial growth. Human conjunctival tissues were subjected to a decellularization process involving hypotonic detergent and nuclease buffers. Variations in sodium dodecyl sulfate concentration (0.05–0.5%, w / v ) were tested to determine the appropriate concentration of detergent buffer. DNA quantification, collagen denaturation, cytotoxicity and tensile strength were investigated. Human conjunctival cell growth by explant culture on the decellularized tissue substrate was assessed after 28 days in culture. Samples were fixed and paraffin embedded for immunohistochemistry including conjunctival epithelial cell markers and extracellular matrix proteins. Conjunctival tissue from 20 eyes of 10 donors (age range 65–92 years) was used. Decellularization of human conjunctiva was achieved to 99% or greater DNA removal ( p < 0.001) with absence of nuclear staining. This was reproducible at the lowest concentration of sodium dodecyl sulfate (0.05% w / v ). No collagen denaturation ( p = 0.74) and no difference in tensile strength parameters was demonstrated following decellularization. No significant difference was noted in the immunolocalization of collagen IV, laminin and fibronectin, or in the appearance of periodic acid–Schiff‐stained basement membranes following decellularization. The decellularized tissue did not exhibit any cytotoxicity and explant culture resulted in the growth of stratified conjunctival epithelium. Allogeneic decellularized human conjunctiva can be successfully decellularized using the described protocol. It represents a novel substrate to support the expansion of conjunctival epithelium for ocular surface cellular replacement therapies. Copyright © 2017 John Wiley & Sons, Ltd.